Toward A Diet Based on MicroRNA - Raúl Isea (International Journal of Nutrition, 2024)
The purpose of this work is to emphasize the possible benefits of a microRNA-based diet in reducing the negative effects of a number of diseases, such as cancer, diabetes mellitus, obesity, hypertension, chronic respiratory conditions, and others.
Keywords: microRNA